Viral immunity: Basic mechanisms and therapeutic applications—a Keystone Symposia report. Issue 1 (30th January 2023) - Cable, Jennifer; Balachandran, Siddharth; Daley‐Bauer, Lisa P.; Rustagi, Arjun; Antony, Ferrin; Frere, Justin J.; Strampe, Jamie; Kedzierska, Katherine; Cannon, Judy L.; McGargill, Maureen A.; Weiskopf, Daniela; Mettelman, Robert C.; et al.
Abstract: Viruses infect millions of people each year. Both endemic viruses circulating throughout the population as well as novel epidemic and pandemic viruses pose ongoing threats to global public health. Developing more effective tools to address viruses requires not only in‐depth knowledge of the virus itself but also of our immune system's response to infection. On June 29 to July 2, 2022, researchers met for the Keystone symposium "Viral Immunity: Basic Mechanisms and Therapeutic Applications." This report presents concise summaries from several of the symposium presenters. Abstract : Viruses infect millions of people each year. Both endemic viruses circulating throughout the population as well as novel epidemic and pandemic viruses pose ongoing threats to global public health. Developing more effective tools to address viruses requires not only in‐depth knowledge of the virus itself but also of our immune system's response to infection. On June 29 to July 2, 2022, researchers met for the Keystone symposium "Viral Immunity: Basic Mechanisms and Therapeutic Applications." The meeting was held jointly with the symposium "Respiratory Viruses: New Frontiers."